The effects of augmented reality on improving spatial problem solving for object assembly. (October 2018) - Deshpande, Abhiraj; Kim, Inki
Abstract: The capability of Augmented Reality (AR) technology to track and visualize relations of objects in space has led to diverse industry applications to support complex engineering tasks. Object assembly is one of them. For an AR aid to support Ready-to-Assemble (RTA) furniture particularly, the challenge is to effectively design the visual features and mode of interaction, so that the first-time users can quickly conceive spatial relations of its parts. However, AR developers and engineers do not have sufficient guidelines to achieve such performance-driven goals. The scientific evidence and account of how one could cognitively benefit in object assembly can be useful to guide them. This experimental research developed an Augmented Reality (AR) application on the Microsoft HoloLens™ headset, and tested it on the first-time users of RTA furniture. The controlled experiments and behavioral analyses of fourteen participants in working out the two RTA furniture with different assembly complexity showed that, the application was effective to improve spatial problem-solving abilities. Especially, the positive effects of the AR-based supports stood out against the assembly of higher complexity. The findings have implications for the information design of advanced AR applications to support assembly tasks with high demands of spatial knowledge. In addition, the extensive analyses of the participants' performance, behaviors, cognitive workload, and subjective responses helped identify usability issues with the Microsoft HoloLens™.